2006
DOI: 10.1016/j.virol.2005.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Multiple human papillomavirus genes affect the adeno-associated virus life cycle

Abstract: The risk of cervical cancer, one of the most prevalent cancers in the world, is determined by two viruses. Human papillomavirus (HPV) is the main risk factor for developing cervical cancer. However, although little known, it is well substantiated that the human Parvovirus adeno-associated virus type 2 (AAV), and its encoded Rep78 protein, interacts with HPV and lowers the risk of cervical cancer. HPV also contributes to AAV inhibition by serving as a helper virus for AAV and stimulating higher AAV replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…But this was a mild phenotype, not a strong inhibition. This finding of inhibition of AAV transcription is in contrast to our previous studies where E1 was found to be a significant upregulator of rep and cap expression [24]. However, these earlier studies of E1 help were in a fully productive system with wt AAV (simultaneous DNA replication and virion production).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…But this was a mild phenotype, not a strong inhibition. This finding of inhibition of AAV transcription is in contrast to our previous studies where E1 was found to be a significant upregulator of rep and cap expression [24]. However, these earlier studies of E1 help were in a fully productive system with wt AAV (simultaneous DNA replication and virion production).…”
Section: Discussioncontrasting
confidence: 99%
“…This basic work was first carried out in the laboratory in 1984 [6-9] in primary cells/animal models [13-19], and AAV is now one of the top clinical gene therapy vectors in use today [20-22]. While wt AAV will replicate in differentiating keratinocytes [23, 24] and certain cell lines (often with genotoxic stress) [25-28] in the laboratory, in tissue culture, most cell types AAV require co-infection by a helper virus, such as adenovirus (Ad), herpes simplex virus (HSV), or human papillomavirus (HPV), to allow productive AAV infection to occur [24, 29-31]. However, a recent study has shown that AAV is most often not found with associated Ad helper virus in clinical isolates, suggesting that AAV is likely a type of highly tropic (“picky”) regular autonomous parvovirus [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, expression levels declined sharply when the NS1 gene was deleted from the recombinant genome, presumably because of the multiple activities that this densovirus replication initiator protein possesses. These activities include sequence-and strand-specific nicking activity, 19 ATP-dependent helicase activity, 20 and especially promoter transregulation 21,22 that influences the expression of target genes. If NS1 is preserved in its entirety, the size of the inserted sequence is limited to approximately 1,000 bases; this limit excludes most genes for insecticidal proteins.…”
Section: Discussionmentioning
confidence: 99%